Analysis of Sea Water Temperature Change on The Coast of Turkey with GIS and Evaluation of Its Ecological Effects - Erkan Kalıpcı; Volkan Başer; Mustafa Türkmen; Nihal Genç; Hüseyin Cüce (Doğal Afetler ve Çevre Dergisi)
An increase in seawater temperatures can cause ecological problems in aquatic organisms. In the study based on this idea; Turkey's sea surface temperatures were examined on an annual basis and determined increase rate which are chancing along the coasts were evaluated with geographic information systems. The data used in the study were obtained from the Turkish State Meteorological Service of the Ministry of Agriculture and Forestry. Between 1970 and 2019, sea surface temperatures of the Black Sea, Mediterranean, Aegean, and Marmara were examined and the 50-year analysis results were processed in the ArcGIS environment and sea surface temperature maps were prepared along the Turkey’s coasts. As a result of the work; sea surface temperatures averages were continued to increase as close to each other with changing trend in the period from 1970 to 2000, The sea surface temperatures were increased by 0.8°C in the Black Sea, 0.5°C in the Mediterranean, 0.4°C in the Marmara and the Aegean seas between the years 2000-2010, compared to the previous period (1990-1999). The increase in sea surface temperatures means were became evident especially in the 2010-2019 period. When the sea surface temperatures averages were compared between 1970-1979 and 2010-2019; It was observed that the sea surface temperatures averages were increased by 1.2 ° C in the Black Sea and the Mediterranean, 0.9 ° C in the Aegean Sea, and 1.5 ° C in the Marmara Sea. The possible effects of this temperature increase in seawater on ecological balance were discussed.